The impact of the Covid-19 pandemic on worker careers: Do different job opportunities matter? - Mara Buhmann; Laura Pohlan; Duncan Roth (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2025)
This paper exploits that the Covid-19 pandemic came as an unexpected shock that temporarily reduced the ratio of vacancies to seekers. We use this unique setting to understand the importance of job opportunities for the impact of unemployment on workers' careers. Compared to individuals who became unemployed under more benign conditions, we find greater and lasting adverse effects on earnings. We provide evidence that lower job opportunities lead unemployed individuals to take up jobs that are further down the occupation-specific wage distribution. Finally, we substantiate the importance of job prospects by using exogenous variation in the pandemic's effect on occupations. – – In diesem Papier wird die Tatsache ausgenutzt, dass die Covid-19 Pandemie ein exogener Schock war, der temporär das Verhältnis von offenen Stellen zu Jobsuchenden verringert hat. In diesem einzigartigen Setting wird die Bedeutung von Beschäftigungsmöglichkeiten untersucht und inwiefern diese Erwerbskarrieren, die von kürzlicher Arbeitslosigkeit betroffen sind, beeinflussen. Im Vergleich zu Arbeitslosen, die unter günstigeren Bedingungen arbeitslos geworden sind, sind die Effekte auf das Einkommen größer und anhaltend negativ. Es zeigt sich, dass geringere Beschäftigungsmöglichkeiten dazu führen, dass Arbeitslose Beschäftigung weiter unten in der berufsspezifischen Lohnverteilung aufnehmen. Die Größe dieser Effekte hängen invers mit der unterschiedlichen Fähigkeit von Berufen, während Lockdowns zu operieren, zusammen.
Keywords: J23; J62; J64; 330; Economic shocks; Covid-19 pandemic; unemployment; worker careers; occupations